Communicating Haze Crisis Online: Comparing Traditional Media News and New Media Perspectives in Singapore. Issue 7 (3rd October 2019) - Lin, Trisha T. C.
ABSTRACT: To understand haze-related online communication in Southeast Asia, this exploratory study took a mixed method approach to conduct web analysis of online communication during haze crisis in Singapore, followed by textual analysis of traditional and new media content during peak days. First, web analytics showed that Singapore's haze online communication occurred mostly on the Twitter platform with primary negative sentiments. Next, textual analysis results found that majority of traditional media-affiliated news provided informative haze reports and centered on positive measurements taken by government and authorities, similar to Public Information Model for crisis management. In comparison, haze-related new media content had diverse topics reflecting laymen's viewpoints with critical tones and negative sentiments. News portals and blogs used two-way asymmetrical and symmetrical model for crisis management, respectively. Additionally, Social Cognitive Theory's media diversity perspectives were applied to understand people's media choices among traditional and new media during natural crisis with environmental influences.